Reconfiguração dinâmica de projetos de software : um modelo para integrar a gerência de projetos de software com os fluxos organizacionais - Rosito, Maurício Covolan (2014)
Software projects are very dynamic and require recurring adjustments of their project plans. These adjustments can be understood as reconfigurations in the schedule, in the resources allocation and other design elements. The large amount of information that the project manager must deal, combined with the frequent changes in the scope and planning, makes this activity more challenging. In addition, the manager may need to consult other departments in the organization during the execution of a software project. Based on these assumptions, a study was conducted to determine the state of the art of the dynamic reconfiguration of software projects, with emphasis on the integration of project management and organizational workflows, in order to identify the main gaps and challenges of research in this field. To reach this goal a methodology of systematic review was adopted. However, according to the analysis of the results, even the most recent studies did not present a solution that addresses all the problems of dynamic reconfiguration at the same time. In order to contribute to the solution of the noted difficulties, this thesis presents a computational model for dynamic reconfiguration of software projects at runtime, with specific focus on the integration of project activities with activities that are part of the organizational workflows. A software tool was developed to demonstrate and evaluate the results of an experimental study withpostgraduate students of project management. Moreover, this model considers the possibility to simulate software projects scenarios, using Petri nets, in response to events of project reconfiguration.